2018
DOI: 10.1080/03601234.2018.1439814
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individual parameter changes on the outcome of the estimated short-term dietary exposure to pesticides

Abstract: In 2015 a scientific workshop was held in Geneva, where updating the International Estimate of Short-Term Intake (IESTI) equations was suggested. This paper studies the effects of the proposed changes in residue inputs, large portions, variability factors and unit weights on the overall short-term dietary exposure estimate. Depending on the IESTI case equation, a median increase in estimated overall exposure by a factor of 1.0-6.8 was observed when the current IESTI equations are replaced by the proposed IESTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although it has been suggested that this exposure increase may be counterbalanced by the expression of LP data on a body-weight (bw) basis, adjusted LP data are not available at this time to fully assess the validity of this assertion. A preliminary assessment using consumption data from Australia and Europe found limited impact from the LP parameter, and those authors suggest it may not provide the offset originally anticipated . A complete set of publicly available LP/bw data will likely take years to gather, approve, and release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been suggested that this exposure increase may be counterbalanced by the expression of LP data on a body-weight (bw) basis, adjusted LP data are not available at this time to fully assess the validity of this assertion. A preliminary assessment using consumption data from Australia and Europe found limited impact from the LP parameter, and those authors suggest it may not provide the offset originally anticipated . A complete set of publicly available LP/bw data will likely take years to gather, approve, and release.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary assessment using consumption data from Australia and Europe found limited impact from the LP parameter, and those authors suggest it may not provide the offset originally anticipated. 16 A complete set of publicly available LP/bw data will likely take years to gather, approve, and release.…”
Section: ■ Introductionmentioning
confidence: 99%